The reasons for excessive body mass in menopausal women - Bąk-Sosnowska, Monika; Skrzypulec-Plinta, Violetta (Menopause Review/Przegląd Menopauzalny, 2012)
Excessive weight gain in women during menopause is a common phenomenon. It leads to the development of abdominal obesity, which together with co-occurring insulin resistance, dyslipidemia and hypertension forms a menopausal metabolic syndrome. Excessive weight gain increases the risk of cardiovascular diseases, which cause fifty percent of deaths of women during menopause. The article is an attempt to answer the question what the basis of menopausal obesity is and whether it is possible to prevent it. The article describes the biological factors and the basic factors related to lifestyle – dietary habits and physical activity. There are also presented psychological factors which affect the somatic state and, indirectly, the lifestyle – beliefs about menopause, the presence of anxiety disorders and depression, sexual activity, relationship with a partner, one’s own body image, personality and temperamental factors. The analysis of the research shows that menopause is characterized by a biologically conditioned predisposition to gain body fat and to accumulate it in the abdomen area. At the same time modification of the lifestyle and the constructive solving of psychological problems limit the development of obesity and help to treat it effectively. Therefore, it is postulated that women in the menopause period should be provided with comprehensive support – medical, dietary, and psychological.